2012
DOI: 10.5005/jp-journals-10018-1040
|View full text |Cite
|
Sign up to set email alerts
|

Features of Hormonal Disturbances in Cirrhotic Patients with Hepatic Encephalopathy

Abstract: Background: Features of hormone disturbances in patients suffering from chronic hepatic failure have been documented for many years. Objective:To evaluate the possible diagnostic and prognostic values of cortisol, total T3, thyroid-stimulating hormone (TSH) and prolactin concentrations in cirrhotic patients for prediction of hepatic encephalopathy (HE) and severity of hepatic diseases. Materials and methods:Study was carried out on 75 (40 males, 35 females) cirrhotic patients (HCV positive) with HE and 50 (28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a study conducted by Arafa et al . [9] , it was shown that individuals diagnosed with hepatic encephalopathy had elevated levels of prolactin, with a positive correlation between the severity of encephalopathy and the magnitude of prolactin rise. In the current research, the assessment of individuals suffering from end-stage liver disease was effectively conducted using the Model for MELD score, which exhibits a positive correlation with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Arafa et al . [9] , it was shown that individuals diagnosed with hepatic encephalopathy had elevated levels of prolactin, with a positive correlation between the severity of encephalopathy and the magnitude of prolactin rise. In the current research, the assessment of individuals suffering from end-stage liver disease was effectively conducted using the Model for MELD score, which exhibits a positive correlation with mortality.…”
Section: Discussionmentioning
confidence: 99%